Non-seatbelt use and associated factors among Thai drivers during Songkran festival - Siviroj Penprapa; Peltzer Karl; Pengpid Supa; Morarit Sompong (BMC, 2012)
Abstract Background Road traffic accidents are the second largest cause of burden of disease in Thailand, largely attributable to behavioural risk factors including drinking and driving, speeding, substance abuse and failure to use seatbelts. The aim of this study was to assess the prevalence and associated factors of non-seatbelt use among drivers during Songkran festival in Thailand. Methods A cross-sectional survey has been performed to determine the prevalence of seatbelt use among Thai drivers (N=13722) during four days of the Songkran festival. For this sample the population of drivers was consecutively selected from 12 petrol stations in four provinces from each of the four main geographical regions of Thailand. The study was conducted at petrol stations at roads in town, outside town and highway at different time intervals when trained field staff administered a structured questionnaire and performed an observation checklist on seat belt use. Results An overall prevalence of 28.4% of non-seatbelt use among drivers was found. In multivariable analysis demographics (being male, younger age, coming from the Northern or Southern region in Thailand), environmental factors (earlier during the Songkran festival, in the morning and late evening and on main roads in town), seatbelt use experiences and attitudes (having been in an accident before, never having used a seatbelt, no intention to use a seatbelt, lack of awareness of danger of non-seatbelt use and lower perceived risk of being caught with non-seatbelt use) and lower exposure to road safety awareness (RSA) campaign (less frequent exposure to RSA campaign, less frequent following of RTI statistics and not talking with others about the RSA campaign) were associated with non-seatbelt use. Conclusion Rates of non-seatbelt use by Thai drivers during Songkran festival was 28.4%. Lower exposure to the RSA campaign was found to be associated with non-seatbelt use among drivers during the Songkran festival.